2013
DOI: 10.1175/waf-d-12-00120.1
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Biweekly Mode and Its Modulation on the Diurnal Rainfall in Taiwan Forecasted by the CFS

Abstract: The occurrence of diurnal afternoon convection in Taiwan undergoes substantial modulation from tropical intraseasonal oscillations in the western North Pacific, including the quasi-biweekly (QBW) mode. By analyzing surface station observations and the Climate Forecast System (CFS) Reanalyses (CFSR), as well as the NCEP CFS version 2 (CFSv2) reforecast data over 18 summers from 1993 to 2010, it was found that the QBW mode plays a significant role in the formation of episodic diurnal convection. When the cycloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 42 publications
(31 reference statements)
1
19
0
Order By: Relevance
“…Among these weather systems, convective afternoon rainfall (hereafter, CAR) is the most frequently observed pattern (Wang and Chen 2008). Because of its importance to local residents, the characteristics and causes of CAR have been examined in many studies (Chen et al 1991;Johnson and Bresch 1991;Kerns et al 2010;Lin et al 2011;Huang and Chan 2012;Wang et al 2013). Studies have noted that CAR generally occurs on a day associated with a stronger sea breeze circulation during the daytime (e.g., Lin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among these weather systems, convective afternoon rainfall (hereafter, CAR) is the most frequently observed pattern (Wang and Chen 2008). Because of its importance to local residents, the characteristics and causes of CAR have been examined in many studies (Chen et al 1991;Johnson and Bresch 1991;Kerns et al 2010;Lin et al 2011;Huang and Chan 2012;Wang et al 2013). Studies have noted that CAR generally occurs on a day associated with a stronger sea breeze circulation during the daytime (e.g., Lin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Using a local pressure index different from the BSISO2 index, Wang et al . () also demonstrated that DC appears more frequently in Taiwan when the subtropical high east of Taiwan has intensified under the modulation of a higher‐frequency (i.e. 8–25 day) intra‐seasonal oscillation.…”
Section: Resultsmentioning
confidence: 99%
“…However, because the index used by Wang et al . () is different to the two BSISO indices provided by Lee et al . (), it is not possible to clarify the following three scientific questions based on the result of Wang et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations